Implementación de un taller de producción escrita en francés como lengua extranjera empleando las TIC - Luna Espinoza, Olivia (2022)
The development of writing skills requires innovative didactic initiatives for students to achieve significant learning achievements. Thus, we implemented a virtual French writing workshop as a foreign language. We carried out a longitudinal study with the aim of knowing the effectiveness of the workshop with 10 participants (8 women and 2 men) with an average age of 22,4 years (SD ±1,6). The implementation of the workshop, in its pilot phase, was effective from the point of view of the students of the language center of a Mexican university. Future research will expand the sample.